The effects of Biochar additive on the properties of Geopolymer materials - Phitchayanin Khamlue (2019)
© 2019 Trans Tech Publications, Switzerland. In this research, the effects of biochar additive on the properties of geopolymer materials were investigated. Normally, the geopolymer can be used for adsorption materials due to good ion exchange capacity. Biochar also has the application as an adsorption material for pollutant removal. Biochar particles were prepared from waste materials in pyrolysis condition. The geopolymer materials were prepared by mixing metakaolin and aluminium oxide in alkaline activator solutions of Na2SiO3 and NaOH. Biochar was mixed with geopolymer by 0, 10, 20, and 30 % weight of binder. A NaOH concentration of 15 M, and Na2SiO3/NaOH ratios of 1.5 by weight were used. The density, porosity, and water absorption were measured. The phase formation, microstructure, and bonds of the sample were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The adsorption capacity of each sample was determined by methylene blue adsorption tests. The result of the removal efficiency of all samples shows high adsorption capacity (60-70 %). It should be interesting alternative materials used for remove of aqueous solution.